2011
DOI: 10.1007/s00234-011-0995-3
|View full text |Cite
|
Sign up to set email alerts
|

The persistent trigeminal artery: development, imaging anatomy, variants, and associated vascular pathologies

Abstract: The persistent trigeminal artery (PTA) is the most common and most cephalad-located embryological anastomosis between the developing carotid artery and vertebrobasilar system to persist into adulthood. As such, it is frequently reported as an incidental finding in computed tomography angiography and magnetic resonance angiography studies. Here, we review the embryology, anatomy, and angiographic imaging findings, including important variants of this commonly encountered cerebrovascular anomaly (reported incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 96 publications
0
87
0
5
Order By: Relevance
“…In patients undergoing vascular examinations, PTA and its variants are reported with a frequency of 0.1-1%, depending on the imaging modality used [3,17]. In early angiographic studies, the frequency of PTA in examined groups was approximately 0.2% [25]; however, in newer reports this number is significantly higher.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients undergoing vascular examinations, PTA and its variants are reported with a frequency of 0.1-1%, depending on the imaging modality used [3,17]. In early angiographic studies, the frequency of PTA in examined groups was approximately 0.2% [25]; however, in newer reports this number is significantly higher.…”
Section: Introductionmentioning
confidence: 99%
“…In rare cases PTA can contribute to cerebral stroke, which may be induced with thrombotic changes or steal syndrome [1]. The presence of PTA may also be associated with a higher likelihood of concomitant vascular pathologies, such as: arteriovenous malformations, carotid cavernous fistulas, moyamoya disease or abnormalities of the aortic arch and its branches [3,9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in case of hypoplastic or occluded VA, the only endovascular access route to the BA and its branches would have been through ICA-PTA. Likewise, BA-PTA becomes an invaluable endovascular route to the anterior circulation in case of ICA occlusion (Meckel et al, 2013). During brain angiography, PTA was filled both after carotid and vertebral injection, allowing for bidirectional blood flow.…”
Section: Persistent Trigeminal Arterymentioning
confidence: 99%
“…-A medial or sphenoid group, in which the artery arises from the posteromedial aspect of the cavernous ICA coursing medial to the abducens nerve, close or into the sella turcica, and pierces the dura of the dorsum sellae. Besides being exposed to iatrogenia during sellar surgery, this variation is associated with transient ischemic attack of the posterior fossa, with symptoms such as dizziness, vertigo, gait disturbance and ataxia (Salas et al, 1998 Meckel et al, 2013). Although early reports stated there was an association between PTA and other intracranial aneurysms, a large MR angiographic study over 16415 patients concluded there was no difference in intracranial aneurysms incidence among patients with and without PTA (O'uchi and O'uchi, 2010).…”
Section: Persistent Trigeminal Arterymentioning
confidence: 99%
See 1 more Smart Citation